Sexual differences in physical exercise: frequency, duration and type of exercise (UNED Research Journal, 2023)
ABSTRACT: "Sexual differences in physical exercise: frequency, duration and type of exercise". Introduction: Physical exercise is any activity programmed and carried out on a regular basis. It is considered a determining factor of prevention. Usually, reported exercise levels do not match trends in cardiovascular diseases and other pathologies associated with sedentary lifestyle. Objective: To test the hypothesis that there are differences between men and women in frequency, duration and type of exercise. Methods: We applied an online survey was applied to the staff of a Costa Rican university (N=3 998 persons) from October 1, 2021 to March 1, 2022 (45% filled it out). Results: Men exercise more than women, but women exercise longer. Men prefer strength exercises such as weight lifting, while women focus on flexibility, rhythm and coordination. Additionally, people with higher education and job positions exercise more. Conclusion: Sex, education and job position correlated with exercise type and frequency.